Prevalence of depression among school going adolescents in India: a systematic review and meta-analysis of cross-sectional studies - Kamath, Prashanthi; Dsouza, Sushma Marita; Mahapatra, Subhransu; Jayakumar, Sruthi (International Journal Of Community Medicine And Public Health, 2021)
The objective of this systematic review was to estimate the pooled prevalence of depression among schoolgoing adolescents in India by using Beck’s Depression Inventory (BDI 1 or BDI 2). A systematic literature search was conducted in PubMed, Ovid MEDLINE, Ovid EMBASE, CINAHL, Cochrane Library, PsycINFO and Google Scholar to identify cross-sectional school-based studies published during 1990-2020. Studies with pre-identified mental illness were excluded. Heterogeneity between studies were examined and estimates were pooled using a random-effects model. Subgroup and sensitivity analysis were performed. Publication bias was evaluated using funnel plot and Egger’s test. We included 13 studies in the meta-analysis. The random effect meta-analysis revealed that the pooled prevalence of depression among school going adolescents was 53% (95% CI: 41% - 65%). By gender, the prevalence was 50% (95 % CI: 38%–62%) in males and 57% (95% CI: 46% - 69%) in females. The subgroup analysis revealed that the pooled prevalence increased with the education levels (High school: 42%; High school and pre-university: 55%; and Pre-university: 67%). In this review we found that more than half of the school going adolescents in India suffered from depression that ranged from mild to severe. These results draw attention to re-look at the mental health policy and newer public health approaches to address depression. Further, strengthening school-based mental health services, along with the community and center-based care is crucial to prevent and effective management of depression among adolescents.